Ehlers-Danlos syndromes and their manifestations in the visual system - Asanad, Samuel; Bayomi, May; Brown, Douglas; Buzzard, Joshua; Lai, Eric; Ling, Carlthan; Miglani, Trisha; Mohammed, Taariq; Tsai, Joby; Uddin, Olivia; Singman, Eric (Frontiers in Medicine, 2022)
Ehlers-Danlos syndrome (EDS) is a rare, genetically variable, heterogenous group of (currently recognized) thirteen connective tissue disorders characterized by skin hyperextensibility, tissue fragility, and generalized joint hypermobility. In addition to these commonly recognized phenotypes, recent studies have notably highlighted variable ophthalmic features in EDS. In this review, we comprehensively gather and discuss the ocular manifestations of EDS and its thirteen subtypes in the clinical setting.